Sustainability in Construction: A Quantity Surveyor's Perspective on Green Building Practices - Olabanji M. KADI (FUDMA Journal of Engineering and Technology, 2025)
Green costing is one of the new niches for the quantity surveying profession. With the advancement of technologies and mechanisms, integrating costs and other relevant data can be done to ensure greater financial transparency for projects. This study assesses a quantity surveyor's perspective on green building practices. The study targeted 46 registered quantity surveying firms in Abuja, Nigeria, according to the Nigerian Institute of Quantity Surveyors [NIQS] Directory. Three respondents were sampled from each firm, which include principal partners, senior quantity surveyors, and junior quantity surveyors.  A quantitative research approach was thus employed, with the use of a questionnaire to collect data from 138 respondents consisting of quantity surveyors. The data analysis was performed using frequency count, percentage, mean item score, and standard deviation. Findings from the study revealed that 23.9% of respondents indicated awareness of green building, while 76.1% showed a lack of awareness. Furthermore, the findings reveal that 50.0% of the respondents believed that the current state of sustainable practices was significant. The most important challenges and barriers to the adoption of green building practices are a lack of government incentives, a lack of effort by local construction industry professional bodies, and a lack of stakeholder empowerment, with MIS = 4.40, 4.40, and 3.85 ranked 1st, 2nd, and 3rd, respectively. The findings concluded that, from a quantity surveyor's perspective, the current state of sustainable practices in the construction industry is increasingly significant and evolving. The research suggests that to facilitate a seamless shift towards sustainable green building, it is essential for players in the industry to actively investigate and embrace sustainable principles, particularly in the first phases of project design.
Keywords: Building, construction, green practices, quantity surveyor's, sustainability.